2022
DOI: 10.1101/2022.03.04.22271541
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automatic Extraction of Social Determinants of Health from Medical Notes of Chronic Lower Back Pain Patients

Abstract: Background. Adverse social determinants of health (SDoH), or social risk factors, such as food insecurity and housing instability, are known to contribute to poor health outcomes and inequities. Our ability to study these linkages is limited because SDoH information is more frequently documented in free-text clinical notes than structured data fields. To overcome this challenge, there is a growing push to develop techniques for automated extraction of SDoH. In this study, we explored natural language processin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In previous works, SDOH have been extracted from clinical data using different methods. These state-of-the-art methods can be categorized into conventional methods like regular expressions, dictionaries or rule-based like cTAKES 33,34 , or deep neural networks like CNN, LSTMs 35 and the latest Transformer based methods 34 . Surprisingly, in the large training sets, language model-based representations outperformed other trained neural nets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous works, SDOH have been extracted from clinical data using different methods. These state-of-the-art methods can be categorized into conventional methods like regular expressions, dictionaries or rule-based like cTAKES 33,34 , or deep neural networks like CNN, LSTMs 35 and the latest Transformer based methods 34 . Surprisingly, in the large training sets, language model-based representations outperformed other trained neural nets.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6: COVID-19 hospitalization by race and ethnicity.DISCUSSIONPrevious works: Previous works have extracted SDOH information from clinical data using different methods such as regular expressions, dictionaries, rule-based methods like cTAKES[41,42], and deep neural networks like CNNs, LSTMs[43], and Transformer-based methods[42]. Language model-based representations have been found to perform well, especially with large training sets.…”
mentioning
confidence: 99%
“…Firstly, many studies have focused on a limited set of SDoH factors. The review [22] revealed that among the 82 methods examined, only three SDoH factors were commonly addressed: smoking status (27 methods), substance use (21), and homelessness (20). Other critical factors such as education, insurance status, and broader social issues are still in the developmental stage.…”
Section: Related Workmentioning
confidence: 99%
“…Notably, Patra et al conducted a comprehensive review of 82 NLP methods aimed at identifying SDoH [22]. These methods span various approaches, from rule-based to deep learning-based methods, presenting the identification of SDoH as either a classification problem [16 18 19] or a named entity recognition (NER) problem [15 20 21]. For example, Stemerman et al [18] designed a multi-label classifier to identify six SDoH categories within sentences extracted from clinical notes sourced from the University of North Carolina’s clinical data warehouse.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation